Ketersediaan Jaringan Prasarana Distribusi Listrik Di Wilayah Permukiman Bumi Tamalanrea Permai Kota Makassar - Faisal Faisal (Politeknik Negeri Ujung Pandang, 2011)
The aim of the study was to explain the effect of the availability of infrastructure, service, and customer participation on the performance of electrical distribution at Bumi Tamalanrea Permai and the most dominant factor affecting the performance. The study was descriptive quantitative. The data were collected through interview and questionnaire. The results of the study indicate that the availability of infrastructure, service and public participation are affected by several factors: availability of electrical infrastructure outside and inside the house and public road illumination. The role of workers has a great effect on the reliability of electrical system, public/customer participation in paying the electric bill, report to the workers in charge when there is a problem of outage, arid make an effort to public road illumination, are real contribution of community to create the reliability of electrical system at Bumi Tamalanrea Permai settlement in Makassar city.